Antidiabetic effect of fucoxanthin extracted from Sargassumangustifolium on streptozotocin‐nicotinamide‐induced type 2 diabetic mice. Issue 7 (6th May 2021) - Oliyaei, Najme; Moosavi‐Nasab, Marzieh; Tamaddon, Ali Mohammad; Tanideh, Nader
Abstract: This work aimed to study the antidiabetic effect of encapsulated fucoxanthin with porous starch (PS) in streptozotocin and nicotinamide‐induced type 2 diabetic mice. Fucoxanthin was extracted and purified from Sargassum angustifolium and encapsulated in porous starch (PS). Diabetic mice groups were gavaged daily with fucoxanthin (400 mg/kg), either free or encapsulated into PS, and metformin (50 mg/kg) for three weeks. The results exhibited that the fucoxanthin and fucoxanthin‐loaded PS markedly prevented the weight gain in treated groups ( p < .05). Moreover, both free and encapsulated fucoxanthin could decrease the fasting blood glucose and increase the plasma insulin level similar to metformin ( p < .05). In addition, total cholesterol, triglyceride, and low‐density lipoprotein were lower in the treated groups. These results confirm antiobesity effect of fucoxanthin by regulating lipid profile parameters. Moreover, the histopathology evaluation of pancreatic tissue in diabetic mice exhibited that oral administration of metformin and fucoxanthin caused regeneration of pancreatic beta cells. This study revealed the healthy effect of seaweed pigment as a suitable bioactive compound which can be used in functional foods for natural diabetes therapy. Abstract : This study revealed the healthy effect of seaweed pigment, fucoxanthin, as suitable bioactive compound which can be used in functional foods for natural therapy. This study confirmed the antidiabetic activity of fucoxanthin in STZ‐induced diabetic mice model.